Survival and financial performance of Japanese subsidiaries in Malaysia and Thailand - Mohamad, Norhidayah; Hoshino, Yasuo (2012)
This paper empirically examines the effects of Japanese parent financial performance with interactions on the Japanese foreign subsidiaries financial performance. We used Japanese outward Foreign Direct Investment (FDI) with a panel data of two ASEAN countries that received the highest Japanese FDI for the period 2003 until 2009. The purpose of this paper is to establish a relationship that is statistically significant with regard to the performance of Japanese subsidiaries located in Malaysia and Thailand using the ORBIS database. A multiple regression model has been applied in this research and the results reveal that some parent’s financial ratios have influence on the subsidiaries financial performance. Moreover, the parent company’s ‘R&D per operating value’, ‘profit margin,’ and ‘solvency ratio’ are the best indicators of the performance of the subsidiaries in the two-host countries.